A study of community design, greenness, and physical activity in children using satellite, GPS and accelerometer data - Almanza, Estela; Jerrett, Michael; Dunton, Genevieve; Seto, Edmund; Ann Pentz, Mary (Health & place, 2012)
This study examined relationships between greenness exposure and free-living physical activity behavior of children in smart growth and conventionally designed communities. Normalized Difference Vegetation Index (NDVI) was used to quantify children's (n=208) greenness exposure at 30-s epoch accelerometer and GPS data points. A generalized linear mixed model with a kernel density smoothing term for addressing spatial autocorrelation was fit to analyze residential neighborhood activity data. Excluding activity at home and during school-hours, an epoch-level analysis found momentary greenness exposure was positively associated with the likelihood of contemporaneous moderate-to-vigorous physical activity (MVPA). This association was stronger for smart growth residents who experienced a 39% increase in odds of MVPA for a 10th to 90th percentile increase in exposure to greenness (OR=1.39, 95% CI 1.36–1.44). An individual-level analysis found children who experienced >20min of daily exposure to greener spaces (>90th percentile) engaged in nearly 5 times the daily rate of MVPA of children with nearly zero daily exposure to greener spaces (95% CI 3.09–7.20). ► We examine relationships between greenness exposure and children's physical activity. ► We analyze GPS, accelerometer, and NDVI data, and address spatial autocorrelation. ► Greenness exposure is positively associated with moderate-vigorous physical activity. ► Greenness effect is stronger for smart growth vs. conventional community residents